AB0394 Tapering tnf inhibitors in rheumatoid arthritis: a retrospective study. (15th June 2017) - Hacioglu, A; Hatemi, G; Esatoglu, SN; Ozguler, Y; Ugurlu, S; Seyahi, E; Melikoglu, M; Fresko, I; Ozdogan, H; Yurdakul, S; Hamuryudan, V
Abstract : Background: Increasing evidence suggests the feasibility of biologic DMARD tapering in RA patients after achieving and maintaining good control of disease activity. Current guidelines on RA treatment also recommend tapering of biologic and non-biologic DMARDs for patients in remission. Data on biologic DMARD tapering reflecting real life settings are limited. Objectives: To collect information on biologic DMARD tapering and its outcome in RA patients who are followed-up in a rheumatology outpatient clinic. Methods: In this retrospective study we used the hospital administrative database to identify patients with a diagnosis of RA and a first time prescription of a biologic DMARD that was specifically limited to one of the 3 TNF inhibitors (etanercept, adalimumab, infliximab) between January 2012 and the end of December 2013. Demographics and information regarding treatment and outcome were taken from the medical charts. Results: Of the 125 patients identified at the database search, 104 were belonging to our clinic and had available follow-up data until June 2016. Seventy-nine of them were women and 25 were men. Their mean age was 47.7±13 SD years and their mean disease duration was 7.4±6.9 SD years. 60% were prescribed etanercept, 23% adalimumab and 17% infliximab. After a mean duration of 14.0±7.6 SD months a dose reduction of TNF inhibitors was made in 44 patients (42%). This was in the form of spacing in 39 patients (Etanercept =16, Infliximab =14, Adalimumab =9) and dose tapering in 5 (all Etanercept). All of these were due to good clinical response except for 1 patient's own request for fear from adverse effects. Following dose reduction increased disease activity was seen in 16 patients (36%) mandating restoration to original dose within a mean of 8.8±9.7 SD months with good response. Twenty-eight patients (64%) preserved their good clinical response during a mean follow-up of 46.1±6.3 SD months which enabled further dose reductions in 20 patients. There was also reductions in the mean number of synthetic DMARD's (1.4±0.8 SD at the initiation of TNF inhibitors and 0.7±0.8 SD at the end of follow-up) and in the percentage of patients using steroids (78% to 33%). At the end of the follow-up, among the whole group of 104 patients, only 73 (70%) were using biologics (TNF inhibitors =49, non-TNF biologics =24). The reasons for stopping biologics in the remaining 31 patients were ongoing remission (16 patients), pregnancy (1 patient), non-compliance (4 patients), injection site reactions (3 patients), fear from adverse events (1 patient), deciding to try complementary medicine (1 patient) and other issues such as losing insurance and family issues (5 patients). Conclusions: Tapering of TNF inhibitors was possible in 40% of RA patients during their routine follow-up. Half of the patients maintained good clinical response after tapering allowing further dose reductions in one third. Disclosure of Interest: None declared